A CFD based optimization procedure of operating parameters for an impinging jet on moving fabric subject to thermal dipping process - Ben Hamida, Mohamed Bechir; Mohsen, Ali M.; Hussein, Muntadher Abed; Rajab, Husam; Chamkha, Ali (International communications in heat and mass transfer, 2025)
A numerical study was conducted to investigate the flow and heat transfer characteristics in a thermal processing jet box oven, typically used in the textile and tire manufacturing industries. The internal enclosure of the jet box was optimized in four consecutive steps by varying the distance between the jet nozzles, the distance between the jet nozzle tip and the impinged fabric, the jet confinement, and also the ratio of the jet velocity to the fabric movement velocity. To quantify the influence of each parameter and to define optimum operating condition, a non-dimensional parameter, ηT, was introduced as a measure of the thermal uniformity of the fabric compared to a reference case. It was found that increasing the distance between the jet nozzles leads to an increase in thermal uniformity of the fabric and to a decrease in the maximum normal stress imposed on the fabric. The results also demonstrated that increasing the distance between the jet nozzle tip and the impinged fabric leads to an improved thermal uniformity of the temperature distribution on the fabric and the jet confinement configuration has a significant influence on the temperature distribution of the fabric. An optimum value for the jet confinement parameter exists. The ratio of the jet velocity to the fabric movement velocity was shown to have a direct impact on the temperature distribution of the fabric and on the maximum normal stress on the fabric. With the increase in the velocity of the impinging jet, the temperature of the fabric and the normal pressure force imposed on its sides were found to increase. Overall after optimizing the operating conditions, the thermal uniformity in the fabric was improved by 84.45 %, as compared to a reference case.